2001
DOI: 10.12968/ijpn.2001.7.4.9032
|View full text |Cite
|
Sign up to set email alerts
|

Young adults with cancer: the effect of the illness on parents and families

Abstract: This article is based on the findings from a qualitative study involving a collection of narratives written by the parents of young adults with cancer. It examines the effects of the illness on parents and family and illustrates that young people aged 18-25 years face particular difficulties when diagnosed with a life-threatening illness. The article focuses on how these difficulties are experienced by the parents of young adults who are attempting to maintain 'normality' and perhaps also manage newly establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 7 publications
0
37
0
1
Order By: Relevance
“…Aspects of the parents' experiences can depend on the nature of the relationships between the child and the parent and how the child wanted to involve their parents, described in the literature by others [3,16]. Therefore, these relationships can vary and will have an influence on whether the aging parent can participate and share feelings and thoughts about the situation with the adult child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspects of the parents' experiences can depend on the nature of the relationships between the child and the parent and how the child wanted to involve their parents, described in the literature by others [3,16]. Therefore, these relationships can vary and will have an influence on whether the aging parent can participate and share feelings and thoughts about the situation with the adult child.…”
Section: Discussionmentioning
confidence: 99%
“…When the adult child moved back to their parents' home they needed more support with their personal needs. Grinyer and Thomas [16] posed that the newfound independence of the adult child was threatened by them having to be dependent on the parents again. For those younger adult children who were cured, there was a phase when they, like they did earlier in the life, moved to an independent life again.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, younger adult caregivers are more likely to experience greater distress when encountering their new role as a cancer caregiver. While a limited number of studies have reported heightened levels of psychological distress and unique health care needs among young adult cancer patients and survivors [5,21,39,43], inquiries concerning younger cancer caregivers have yet to be reported in the literature.…”
mentioning
confidence: 99%
“…Respondents were offered a choice of face-to-face interview, writing a letter or recording their experiences onto cassette, methods previously used to investigate the effects of illness on parents of young people with cancer (Grinyer & Thomas, 2001). Those writing a letter or making a recording were asked to respond to the questions on the topic guide sent with the invitation letter.…”
Section: Table One About Herementioning
confidence: 99%